1992
DOI: 10.1037/h0078709
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving control, construing benefits, and daily processes in rheumatoid arthritis.

Abstract: To examine the influence of perceived pain control and pain benefit appraisals on adjustment to rheumatoid arthritis (RA), we followed fifty-four RA patients for seventy-five days. After completing measures of dispositional optimism and appraisals of control over, and benefits from, their chronic pain, participants reported each day their pain intensity, mood, and activity limitations due to pain. Controlling for disease activity and dispositional optimism, those who believed they had more control over their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
1
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(123 citation statements)
references
References 59 publications
9
105
1
8
Order By: Relevance
“…Some of these instruments are symptom-specific (19,24,25) and, hence, do not allow comparisons between groups with different symptoms. An example of a disease-specific instrument is the Perceived Control and Benefits Questionnaire (25), designed to measure personal control and the perception of benefits in patients with chronic pain. Other measures assess the constructs in a trait-like fashion unrelated to specific situations such as chronic illnesses (26,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these instruments are symptom-specific (19,24,25) and, hence, do not allow comparisons between groups with different symptoms. An example of a disease-specific instrument is the Perceived Control and Benefits Questionnaire (25), designed to measure personal control and the perception of benefits in patients with chronic pain. Other measures assess the constructs in a trait-like fashion unrelated to specific situations such as chronic illnesses (26,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, having challenging, stimulating work and having control over one's pace, schedule, and activities may give one a feeling of control over the events that occur, as Karasek and Theorell (1990) suggest, or it may offer real options for action that help to neutralize the effect of a negative event. Workers in structural locations that offer such control may also be individuals who happen to possess a personal sense of control irrespective of their social location (see Tennen et al, 1992 for a review of this literature). The effortreward imbalance model of chronic work stress may provide insights into some of these issues, as it includes both a structural and a personal dimension (Siegrist, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In a related study, Tennen et al (1992) distinguished between perceived control (primary control) and perceived benefits (secondary, cognitive control) and found that at high levels of pain the former is related to low mood and the latter with low activity limitations, further supporting the two-process model.…”
Section: Coping and Emotion Regulation -Context-dependence In Chronicmentioning
confidence: 88%